If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + -11 = -1(6 + -6n) Reorder the terms: -11 + n = -1(6 + -6n) -11 + n = (6 * -1 + -6n * -1) -11 + n = (-6 + 6n) Solving -11 + n = -6 + 6n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6n' to each side of the equation. -11 + n + -6n = -6 + 6n + -6n Combine like terms: n + -6n = -5n -11 + -5n = -6 + 6n + -6n Combine like terms: 6n + -6n = 0 -11 + -5n = -6 + 0 -11 + -5n = -6 Add '11' to each side of the equation. -11 + 11 + -5n = -6 + 11 Combine like terms: -11 + 11 = 0 0 + -5n = -6 + 11 -5n = -6 + 11 Combine like terms: -6 + 11 = 5 -5n = 5 Divide each side by '-5'. n = -1 Simplifying n = -1
| 7y=-21-5x | | 4(5x+7)=13 | | 3x-1=5x+2 | | 3x^2+15x+8= | | 19x-37x= | | .06x+x=33310 | | -3(8p+5)-2(1-20p)=3(6+5p) | | 7n-34=-3-6(5n-1) | | 3(x+30)+x(42)+195=390 | | 12(m-3)-1=-(5m+9) | | 4(x-12)=16x | | -9x+14x= | | r=wp | | 2m-2x=x+p | | .02x+x=14280 | | 16x-3x=13x | | 6(1+4b)=-6(4b-4) | | .25z-.75=-.25x+3.25 | | 5y+38+3x=180 | | -9(v+2)+3v+7=6v+8 | | 3w+5k-4w+k= | | 5x^2-7x+37=0 | | 26x+18=5(5x+2) | | -3(3x+7)-5x=29-4x | | 36x^2+25= | | .25z-.75=-.25+3.25 | | 2y=30-8x | | -4n(n-1)=6.5 | | y=1/5+3 | | 5x-6x+9=4x-1 | | 8(r+7)+5r=-5(6+6r) | | -14=s+12/6 |